Cohort profile: indigenous human papillomavirus and oropharyngeal squamous cell carcinoma study - a prospective longitudinal cohort. Issue 6 (3rd June 2021) - Jamieson, Lisa M; Garvey, Gail; Hedges, Joanne; Leane, Cathy; Hill, Isaac; Brown, Alex; Ju, Xiangqun; Sethi, Sneha; Roder, David; Logan, Richard M; Johnson, Newell; Smith, Megan; et al.
Abstract : Purpose: Our aims are to: (1) estimate prevalence, incidence, clearance and persistence of oral human papillomavirus (HPV) infection among Indigenous Australians; (2) identify risk factors associated with oropharyngeal squamous cell carcinoma (OPSCC)-related HPV types (HPV 16 or 18); (3) develop HPV-related health state valuations and; (4) determine the impact on OPSCC and cervical cancers, and the cost-effectiveness of extending publicly-funded HPV vaccination among Indigenous Australians. Participants: Participants were recruited from February 2018 to January 2019. Twelve-month follow-up occurred from March 2019 to March 2020. Participants provided socio-demographic characteristics, health-related behaviours including tobacco and alcohol use and sexual history. Health state preferences in regard to HPV vaccination, knowledge regarding HPV infection, OPSCC and cervical cancer were collected using a two-stage standard gamble approach. Participants provided saliva samples and DNA for microbial genotyping was extracted. Findings to date: Of the 910 participants who were positive for β-globin at baseline, 35% had any oral HPV infection. The most prevalent HPV types were 13 or 32 (Heck's disease; 23%). The second most prevalent types were associated with OPSCC (HPV 16 or 18; 3.3%). Of the 645 participants who were positive for β-globin at 12-month follow-up, 43% had any HPV infection. Of these, 33% were HPV types 13 or 32 and 2.5% were HPV 16 or 18. Some 588 participants had β-globin positive oral samples at baseline and 12-month follow-up. The prevalence of any oral HPV infection increased from 34% at baseline to 44% at 12-month follow-up; due to increases in HPV types 13 or 32 (20% at baseline and 34% at 12-month follow-up). Future plans: Further funding will be sought to continue follow-up of this cohort, and to include (after a full medical history) a thorough clinical examination of the external head and neck; a complete oral examination and examination of the oropharynx. Blood tests for early stage OPSCC will also be undertaken.